2020
DOI: 10.1111/raq.12496
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics and their potential effects on the aquaculture systems: a critical review

Abstract: According to the statistics, 8.3 billion metric tonnes of plastics have been produced since 1950s, which is far more than other synthetic materials and the annual production which are about 500 million tonnes per year at present. The production of plastics makes microplastics pollution extremely widespread distribution, which will have a lasting impact on the global environment, especially on the aquaculture systems. And the distribution of the microplastics is extremely imbalanced around the global waters. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(42 citation statements)
references
References 142 publications
(214 reference statements)
1
31
0
1
Order By: Relevance
“…Outbreaks of the four scyphomedusae in this study commonly occur in areas of Chinese coastal waters with large aquaculture industries. China, as the largest exporter of aquatic products in the world, uses vast areas of sea for aquaculture, diverse aquaculture models (e.g., raft culture, cage culture, and pond culture) and numerous species of aquaculture organisms (e.g., fish, shellfish, shrimp, and sea cucumber) ( Cao et al, 2015 ; Zhou et al, 2020 ). In such conditions, high occurrence of potentially pathogenic bacteria in common scyphomedusae is extremely concerning.…”
Section: Discussionmentioning
confidence: 99%
“…Outbreaks of the four scyphomedusae in this study commonly occur in areas of Chinese coastal waters with large aquaculture industries. China, as the largest exporter of aquatic products in the world, uses vast areas of sea for aquaculture, diverse aquaculture models (e.g., raft culture, cage culture, and pond culture) and numerous species of aquaculture organisms (e.g., fish, shellfish, shrimp, and sea cucumber) ( Cao et al, 2015 ; Zhou et al, 2020 ). In such conditions, high occurrence of potentially pathogenic bacteria in common scyphomedusae is extremely concerning.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation and management of microplastic pollution from non-point sources are more difficult than those for point sources because it is hard to regulate and locate the emission contributors. For example, WWTPs, plastic industries, and fishing activities have been identified as main point sources of microplastic pollution in aquatic environments (Estahbanati and Fahrenfeld 2016;Su et al 2020;Zhou et al 2021). Thus, efforts have been made to reduce the contents of microbeads in PCPs and control microplastic emissions from WWTPs (Lares et al 2018;Ngo et al 2019).…”
Section: Research Challengesmentioning
confidence: 99%
“…Although first raised as an issue by Thompson et al, 2004 [3], microplastics were first discovered in North America in the 1970s in the form of small spheres in plankton off the coast of New England [4]. Subsequently, other researchers also found that these tiny particles were not only in the aquatic environment [5][6][7], but also in soil [8,9], organisms [10][11][12], and even in the atmosphere [13,14]. According to the US National Oceanic and Atmospheric Administration (NOAA) in 2008, plastics smaller than 5 mm in size were identified as microplastics (MPs) [15].…”
Section: Introductionmentioning
confidence: 99%